Simultaneous removal of Cr(VI) and phenol contaminants using Z-scheme bismuth oxyiodide/reduced graphene oxide/bismuth sulfide system under visible-light irradiation. (December 2017) - Chen, Acong; Bian, Zhaoyong; Xu, Jie; Xin, Xin; Wang, Hui
Abstract: An all-solid-state Z-scheme system containing Bi-based semiconductors bismuth oxyiodide (BiOI) and bismuth sulfide (Bi2 S3 ) was constructed on reduced graphene oxide (rGO) sheets through an electrostatic self-assembly method to simultaneously remove aqueous Cr(VI) and phenol. In this Z-scheme that mimicked natural photosynthesis, photoinduced electrons in the conduction band (CB) of BiOI were transferred through rGO and reacted with photoinduced holes in the valence band (VB) of Bi2 S3, which significantly increased its photocatalytic activity. The reduction and oxidation reactions were performed on Bi2 S3 and BiOI photocatalysts, respectively. Furthermore, complex contaminants of coexisting heavy metal Cr(VI) and organic phenol were treated using the system under visible-light irradiation. Results showed that Cr(VI) reduction and phenol oxidation were achieved efficiently with optimum reductive and oxidative efficiencies up to 73% and 95% under visible-light irradiation, respectively. This work provided a promising method of simultaneously removing heavy metals and organic pollutants by using a Z-scheme system with enhanced photocatalytic activity. Graphical abstract: Highlights: The BiOI and Bi2 S3 disperses on RGO sheets during the electrostatic self-assembly. Simultaneous removal of Cr(VI) and phenol contaminants is efficient. Reduction and oxidation processes are excited by two separated photocatalysts. A mechanism for the transmitting of photoinduced carriers is proposed.